Periodic solutions of strongly nonlinear systems with nonclassical right-hand side in the case of a family of generating solutions - Akhmetov, M. U.; Ахметов, М. У.; Ахметов, М. У. (Institute of Mathematics, NAS of Ukraine, 1993)
The problem of the existence of periodic solutions to differential equations with pulse effects on the surfaces and to differential equations with discontinuous right-hand sides close to arbitrary nonlinear ones is studied. The existence of a family of periodic solutions to generating equations is assumed.